The Effect of Dressing in Sharia on Psychological and Social Well-Being: Implications and Risks of Deviation in Modern Society - Hanifah Wafa Firdaus; Muthoifin (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to analyze the influence of Sharia application on psychological and social well-being and explore the implications and risks of deviations in modern society. With the increasing integration of Sharia principles into various aspects of life, understanding their effects on individual and societal well-being is crucial. Theoretical Framework: The theoretical framework is based on social integration theory and psychological well-being models, which help explain how religious principles influence life satisfaction, stress, and social cohesion. Literature Review: A literature review reveals that Sharia's impact on psychological well-being is generally positive, fostering a sense of justice and community, yet it also carries risks of social exclusion and value conflicts in diverse societies. Methods: The study employs a mixed-method approach, combining quantitative and qualitative data. A quantitative survey involving 500 respondents assesses the psychological and social effects of Sharia on life satisfaction, stress levels, and social integration. Additionally, qualitative interviews with 30 stakeholders, including Sharia practitioners, academics, and community members, offer in-depth insights into the societal and individual implications of Sharia application. Results: The results show that while Sharia implementation increases a sense of justice and social support, it may also result in social exclusion, especially in pluralistic contexts, leading to value conflicts among different social groups. Implications: The implications of the findings suggest that Sharia's implementation must be carefully balanced with modern societal needs, promoting fairness and inclusivity. Furthermore, mechanisms to prevent and address deviations from Sharia principles are essential for mitigating potential risks. This research provides valuable insights for policymakers, educators, and the general public in managing Sharia's application effectively. Novelty: The novelty of this study lies in its comprehensive exploration of both the positive and negative impacts of Sharia on psychological and social well-being, offering a nuanced understanding of its role in contemporary society.